Krisis Pembelajaran Bermakna dan Integratif terhadap Penghayatan Nilai-Nilai Keagamaan Peserta Didik di MTs N 1 Banggai - Mohammad Ariswara Rai Djafar; Najamudin Petta Solong; Munira Munira; Fatimah Djafar (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The digital transition at MTs N 1 Banggai has fundamentally altered student learning behaviors, leading to a "meaningful learning crisis" where instant information retrieval replaces deep spiritual reflection. This research explores the underlying factors of this crisis, specifically focusing on how digital culture hinders the internalisation of religious values. Utilizing a qualitative phenomenological design, the study gathered insights from teachers, students, and parents through interviews and direct observations. The findings indicate a significant mismatch between traditional, lecture-based teaching methods and the fast-paced, multitasking habits of modern students. Evidence from school records further reveals that instructional planning prioritizes cognitive mastery over moral-digital ethics, resulting in students practicing religious values only superficially. Consequently, the study advocates for a pedagogical shift toward reflective and contextual PAI models that bridge the gap between religious teachings and daily digital interactions.   Keywords: Meaningful and Integrative Learning, Internalization of Student Religious Values, Digital Learning Culture